LEVELS OF PAIN AND INDEPENDENCE OF DAILY ACTIVITIES (ADL) ON OSTEOARTHRITIS PATIENTS - Fajar Alam Putra; Widiyono widiyono; Atik Aryani; Agung Setyawan (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Patients with osteoarthritis will experience pain and limitation of motion which has an impact on difficulty in performing activities of daily living (ADL). Patients with these conditions also require recovery after total knee replacement surgery to restore normal physical, psychological, social, habitual and daily life activities. This study aims to determine the description of pain levels and independence of activity daily living (ADL). This study uses a descriptive design. The population of this study were all total knee replacement patients, 37 samples were selected using purposive sampling. The results showed that a total of 49.7% experienced severe pain and 84.6% of respondents had activity daily living (ADL) activities that were not independent. Nurses are needed to help improve the health status of ostheoarthritis patients so that the patient's quality of life can be maintained optimally. Avoid diseases that can aggravate and can fulfill daily needs independently. Health agencies need to further improve health promotion regarding the maintenance of independence and efforts to overcome pain levels in ostheoarthritis patients